GOOD LIFE IN ISLAM: INTEGRATING FALTH AND WELL-BEING ÔÇ£FLOURISHING DALAM PERSPEKTIF ISLAMÔÇØ - Rusyda, Arina Ilfa (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2025)
Flourishing is one part of positive psychology and the highest welfare that humans can get. The purpose of this study is to see how Islam views flourishing. In writing this article, I as a researcher and writer use the literature review method to get results and discussions. The researcher used two subjects of students from UIN Mahmud Yunus Batusangkar. The results of this study found that Islam highly recommends its people to implement flourishing with the conclusion to avoid mental pathology and gain welfare in life.